Strategi Dan Tantangan Membangun Jiwa Entrepreneurship Pada Peserta Didik Di SMK Al-Ishlah Cikarang Utara - Satim Hamid; Jon Edy; Rachmat Ramadhani; Erna Nur Ifah; Amin Amin; Anton Cahyono; Fahmi Najib; Tiwi Ayu Lestari (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Entrepreneurship is the ability to perform creativity and innovation that creates a work of value that can be sold. The limited job market is a classic problem that has not yet been resolved due to the continuously increasing population and the scarcity of jobs, thus the unemployment rate in the country continues to increase. Therefore, it is necessary to provide knowledge about entrepreneurship from school. Students at SMK Al-Ishlah North Cikarang are Generation Z, class XII, who will face graduation and thus will determine the next step, whether to look for a job, continue to higher education or start a business. These students should not be confused about what to do after graduation. This Community Service activity takes the theme